Narrator Position and Passions Manifestation in Characters’ Description in Iraqi Women’s Novels: Semiotic Study - Mohye, Eman; Hadi , Salah (Al-Adab Journal, 2024)
The start that the semiotics of passions has brought, led to the creation of new techniques within the semiotic theory. Among these techniques, there was the transition from the states of things to the states of human soul in its different passions, the transition from the semiotics of actions to semiotics of passions.Our research journey included finding the possibility of applying the modern methodology processes on the contemporary Iraqi women’s novels, and how the passions work within the novels from composition and meaning perspectives, trying to reveal the shared pattern between the Iraqi women’s novels in different objective representations. We base our academic research journey on the semiotic methodology in studying the description, both external and internal, and its meanings and effects on the characters’ passions in the Iraqi women’s novels. Description is a composition technique related to narration, it is a time pause in which the narrator stops the narration time and describes the events, place, or the characters in a deeply manner to uncover their lives and their internal and external features.This work was achieved through a research plan starting with a theoretical preface including the narrator position and types of visions, followed by a definition of the description, its functions, places, and the manifestation of passions in it, in addition to its types in the women’s novels in Iraq, specifically from 2003 to 2020.The actual study was divided into two sections upon which the research was based on. The first section, named the external narrator description and its significance on the characters’ passions, and what we concluded as the primary passions in the characters. The second section was devoted to the internal and external narrator description and its significance on characters’ passions. Then, we presented the relation between the two descriptions, followed by the conclusions that include the most important results.